Effect of mesenchymal stem cells on animal semen during storage - E. Yu. Zakirova; A. G. Malanyeva; A. M. Aimaletdinov (Ветеринария сегодня)
Mesenchymal stem cells (MSCs) have been known to mankind since the mid-20th century. The comprehensive study revealed their high biologically active potential. Capacity of forming several types of body tissues was demonstrated. The stem cells, like any other cells, exert their eﬀect on surrounding cells and tissues by secreting extracellular vesicles. The extracellular vesicles of the stem cells possess biological activity of parent cells. Taking into account the regenerative potential of the mesenchymal stem cells, they are currently used in medicine, and also in veterinary medicine for treatment of various injuries of the companion animals. Eﬀect of the mesenchymal stem cells on boar and rat sperm cells during 12-hour storage was studied. The study results demonstrated that during 12 hours of coincubation, the porcine MSCs contributed to the survival of the boar sperm cells and maintenance of their motility at 60–80% (depending on the solvent) as compared to the controls. Such a signiﬁcant eﬀect was not however observed during coincubation of the rat sperm cells with rat MSCs. But it should be noted that before the3rdhour of coincubation, the experimental sperm motility was higher than that of the control. By hour5 of the observation, this diﬀerence was leveled. The rat and boar sperm cells are likely to have diﬀerent physiological characteristics, which were reﬂected in the results obtained. Therefore, possibility of using the MSCs for the storage and cryopreservation of the semen of some animals was demonstrated, but this requires further research.